1997
DOI: 10.1111/1540-5885.1460429
|View full text |Cite
|
Sign up to set email alerts
|

PDMA Research on New Product Development Practices: Updating Trends and Benchmarking Best Practices

Abstract: Product development professionals may have the feeling that yet another buzzword or magic bullet always lurks just around the corner. However, researchers have devoted considerable effort to helping practioners determine which tools, techniques, and methods really do offer a competitive edge. Starting 30 years ago, research efforts have aimed at understanding NPD practices and identifying those which are deemed “best practices.” During the past five years, pursuit of this goal has produced numerous privately a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
890
7
113

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 725 publications
(1,037 citation statements)
references
References 28 publications
27
890
7
113
Order By: Relevance
“…Providing the real product advantages that customers are demanding remains a challenge, despite the acknowledgement that early identification of customers' future needs is a vital stage of new product development (Griffin, 1997;Kahn et al, 2006;Williams and Kochhar, 2000). This may be partly explained by the changing relationship between producers and customers.…”
Section: The Need For Customer Knowledge In New Product Developmentmentioning
confidence: 99%
“…Providing the real product advantages that customers are demanding remains a challenge, despite the acknowledgement that early identification of customers' future needs is a vital stage of new product development (Griffin, 1997;Kahn et al, 2006;Williams and Kochhar, 2000). This may be partly explained by the changing relationship between producers and customers.…”
Section: The Need For Customer Knowledge In New Product Developmentmentioning
confidence: 99%
“…Summarizing the results of the second survey of the Product Development & Management Association's (PDMA's) on companies' new product development best practices, Griffin (1997) reported that 60% of respondents were using some form of stage-gate methodology in their new product development efforts. More recently, in a study conducted for the Institute for Defense Analysis, Atta et al (2012) interviewed R&D leaders of seven large U.S.-based companies: Applied Materials, The Boeing Company, Exxon Mobil Corporation, General Electric, IBM, Intel, and Proctor & Gamble and found that "leading firms use rigorous, but specifically designed stage-gate processes to manage the cost of failure.…”
Section: Introductionmentioning
confidence: 99%
“…Pesquisadores e profissionais de empresas têm dado mais atenção às atividades do pré-desenvolvimento devido a seu impacto na qualidade, no tempo de conclusão do projeto e nos custos de desenvolvimento. Diversos autores discutiram a importância do pré-desenvolvimento para o sucesso dos novos produtos (COOPER; KLEINSCHMIDT, 1995;GRIFIN, 1997;WILEMON, 2002;ERNST, 2002;COOPER et al, 2004c; KAHN; BARCZAK; MOSS, 2006;BACKMAN;BORJESSON;STEN, 2007;WERWORN;HERSTATT;NAGAHIRA, 2008).…”
Section: Introductionunclassified